Biatrial volume, estimated using magnetic resonance imaging, predicts atrial fibrillation recurrence after ablation. Issue 12 (24th October 2018) - Kumagai, Yu; Iwayama, Tadateru; Arimoto, Takanori; Kutsuzawa, Daisuke; Hashimoto, Naoaki; Tamura, Harutoshi; Nishiyama, Satoshi; Takahashi, Hiroki; Shishido, Tetsuro; Yamauchi, Sou; Yamanaka, Tamon; Miyamoto, Takuya; et al.
Abstract: Introduction: The predictive value of left atrial volume (LAV) in atrial fibrillation (AF) is known, but the relationship of right atrial volume (RAV) and biatrial volume (BAV) with AF recurrence after pulmonary vein isolation (PVI) is not clear. Cardiac magnetic resonance (CMR) imaging allows us to more precisely quantify atrial volume. We investigated LAV, RAV, and BAV as predictors of AF recurrence following PVI in AF patients. Methods and Results: We assessed 100 AF patients (age = 59.8 ± 9.5 years, 74 males, 26 females) who underwent nonenhanced CMR before their first PVI. LAV and RAV were measured using CMR. All patients were in sinus rhythm during CMR. BAV was calculated as the sum of LAV and RAV. During the 8‐month follow‐up, AF recurrence occurred in 23 patients. LAV, RAV, and BAV were significantly greater in patients with AF recurrence than in those without (LAV, 103.7 ± 25.8 vs 81.8 ± 24.2 mL, P < 0.001; RAV, 109.4 ± 27.0 vs 82.2 ± 19.6 mL, P < 0.001; BAV, 213.1 ± 46.7 vs 164.1 ± 38.7 mL, P < 0.001). Multivariate logistic regression analysis revealed that increased LAV, RAV, and BAV were significantly correlated with AF recurrence. The area under the receiver operation characteristic curve for BAV showed the largest value compared to that of LAV or RAV alone. Conclusions: LAV, RAV, and BAV were independent predictors of AF recurrence after PVI. Quantifying BAV may additionally improve prognostic stratification compared with LAV or RAV.